PERBANDINGAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN METODE DRILLYANG DIVARIASIKAN DENGAN METODE DISKUSI TERHADAP PEMBELAJARAN BIASA KELAS VII MTI TARUSAN KAMANG - Mirda Swetherly Nurva (STKIP Pesisir Selatan, 2017)
The research was distributed by the low yield learning math grade VII MTI Tarusan Kamang can be seen from the average value of the first semester . Was caused by less-active students in doing the exercises given by the teacher. Therefore to enhance student learning outcomes in this study, researchers used the methods of drill that varied with the method of discussion. Formulation of the problem in this research is whether learning outcomes students use the drill method varied with the method of discussion is better than learning outcomes on the mathematical subjects in grades VII MTI Tarusan Kamang. The hypothesis of this research is the result of learning to use the drill method varied with the method of discussion is better than learning outcomes on the subjects of mathematics Class VII Tarusan Kamang. The purpose of this research is to know whether the results of student learning using the drill method varied with the method of discussion is better than learning outcomes on the subjects of mathematics grade VII Tarusan Kamang. Based on the results of the analysis of test score results of mathematics students in the second grade of the sample, obtained an average classroom experiment = 79.875 S = 9,3198 and class = control 71.5625 S = 7.3990 and L 0.213 = table is obtained. It can be concluded that the results of a study using the method of drill that varied with the method diskuis is better than learning outcomes.